USULAN KRITERIA PENILAIAN KESIAPAN PENERAPAN VENDOR MANAGED INVENTORY (VMI) PADA MATERIAL KAYU DALAM UPAYA MINIMASI STOCKOUT DAN OVER INVENTORY - Dalulia, Primahasmi; Andika Chandra, Gabriel; Putra, Aang Fajar Passa; Erliana, Ken (LENVARI, 2025)
This study aims to propose criteria for assessing the readiness of implementing Vendor Managed Inventory (VMI) for pine wood materials at PT. X to minimize stockout and over inventory. The Kano method was employed to classify supplier criteria into must-be, one-dimensional, and attractive categories. Data were collected through questionnaires filled by five experts from relevant departments. The analysis revealed that must-be criteria include payment terms aligned with the company’s capabilities, ontime delivery, and the supplier’s ability to accommodate demand changes. One-dimensional criteria encompass wood quality compliance and accurate delivery quantity, while attractive criteria involve low wood moisture content, supplier reputation, and responsiveness to schedule changes. The study concludes that supplier readiness in fulfilling must-be criteria is essential for VMI implementation, whereas attractive criteria can enhance company satisfaction. These findings provide a reference for the company in supplier selection and supply chain optimization